2020
DOI: 10.1093/publius/pjaa019
|View full text |Cite
|
Sign up to set email alerts
|

Support for Regionalization in Federal Belgium: The Role of Political Socialization

Abstract: Regionalization, in the form of a dispersion of political power away from national political centers to regional governments, has been a defining feature of European politics since the 1970s. The article focuses on how institutional regionalization changed citizens’ attitudes about the division of competences between the central and regional level. It argues that regional institutions and policies exert a socializing effect on citizens’ preference in favor of these institutions through a mechanism of adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 41 publications
3
15
0
2
Order By: Relevance
“…In line with other research (Svallfors 2010;Neundorf et al 2019;Dupuy et al 2021), the article argues that a substantial part of the explanation of the variation in citizens' support for regionalization lies elsewhere: in their experiences of regionalization. Research on policy feedback offers a stimulating theoretical framework to understand how citizens' experiences of regionalization could impact their support for it.…”
Section: Theorizing Feedback Effects Of Experiences Of Institutional supporting
confidence: 67%
See 4 more Smart Citations
“…In line with other research (Svallfors 2010;Neundorf et al 2019;Dupuy et al 2021), the article argues that a substantial part of the explanation of the variation in citizens' support for regionalization lies elsewhere: in their experiences of regionalization. Research on policy feedback offers a stimulating theoretical framework to understand how citizens' experiences of regionalization could impact their support for it.…”
Section: Theorizing Feedback Effects Of Experiences Of Institutional supporting
confidence: 67%
“…So far, it has been shown that support for regionalization is related to both regional identification and the perception that one's region is economically better off than other regions within the same state (Henderson et al 2014;Verhaegen et al 2018). Moreover, a few studies have suggested that regionalization can have a socializing effect on citizens' attitudes regarding regionalization, but that this effect is moderated by elite discourses politicizing regionalization and putting it in a positive or negative light (Dupuy and Van Ingelgom 2014;Dupuy et al 2021). These studies provide fruitful ground to account for citizens' support for regionalization.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations